Worsening head bleeds in elderly blunt head trauma patients taking antithrombotics: Delayed CT head fails to change management. Issue 1 (January 2019) - Scantling, Dane; Kucejko, Robert; Williamson, John; Galvez, Alvaro; Teichman, Amanda; Gruner, Ryan; Serniak, Nicholas; McCracken, Brendan
Abstract: Background: Most elderly trauma patients suffer blunt head injury and many utilize antithrombotic (AT) medications. The utility of delayed CT-head (D-CTH) in neurologically intact elderly patients using AT who have an intracranial hemorrhage (ICH) on presentation is unknown. We hypothesized that D-CTH would not alter clinical management and aimed to evaluate the role of D-CTH in this population. Methods: A retrospective cohort study was performed. Patients ≥65 years sustaining blunt head injuries from January 2010 to July 2017 were identified using our level 1 trauma center database. AT-patients presenting with ICH who underwent D-CTH were included. Patients with worsened ICH were compared to those with stable to improved ICH on D-CTH. AT-patients were compared to a cohort of non-AT patients. Fisher's Exact and Mann-Whitney U tests were utilized and a power analysis conducted. Results: 137 A T and 34 non-AT patients were identified. There was no difference in hemorrhage progression or appearance of new ICH. No patient had a change in management from D-CTH in either cohort. AT-patients were slightly older (p < 0.001), but cohorts were otherwise similar. 50 AT-patients with worsened ICH were compared to 87 with stable ICH. There was no difference in cohort demographics. Hemorrhage progression did not vary with type of AT used but did increase if multiple types of synchronous ICH were present (p < 0.001). Conclusions: Our data supports abstaining from routine D-CTH of elderly ICH patients with an intact neurologic examination who are utilizing aspirin, clopidogrel or warfarin. Conclusions cannot be drawn regarding new oral anticoagulants (NOACs) given low enrollment. Further multicenter study is required to provide adequate power and detect small levels of management change.